Transactions on edutainment V - Pan, Zhigeng; Cheok, Adrian David; Müller, Wolfgan; Yang, Xub; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This journal subline serves as a forum for stimulating and disseminating innovative research ideas, theories, emerging technologies, empirical investigations, state-of-the-art methods, and tools in all different genres of edutainment, such as game-based learning and serious games, interactive storytelling, virtual learning environments, VR-based education, and related fields. It covers aspects from educational and game theories, human-computer interaction, computer graphics, artificial intelligence, and systems design. The 5th volume in this series represents a selection of 12 contributions from DMDCM 2010, the 5th International Conference on Digital Media and Digital Content Management, held in Chongqing, China, in December 2010, as well as 9 regular papers. The papers cover topics such as human-computer interaction, virtual exhibit, face recognition, character animation etc.; they moreover present a large number of application examples in the area of e-learning, game, animation, multimedia, and virtual reality which gives more broad view on the application of edutainment-related techniques
Innovative Integrated Architecture for Educational Games: Challenges and Merits -- Beyond Standards: Unleashing Accessibility on a Learning Content Management System --  Design and Implementation of an OpenGL Based 3D First Person Shooting Game -- Direct Interaction between Operator and 3D Virtual Environment with a Large Scale Haptic -- Modeling and Optimizing of Joint Inventory in Supply Chain Management -- Vision-Based Robotic Graphic Programming System -- Integrating Activity Theory for Context Analysis on Large Display -- Line Drawings Abstraction from 3D Models -- Interactive Creation of Chinese Calligraphy with the Application in Calligraphy Education -- Outline Font Generating from Images of Ancient Chinese Calligraphy -- Tangible Interfaces to Digital Connections, Centralized versus Decentralized -- Research and Implementation of the Virtual Exhibit System of Places of Interest Base on Multi-touch Interactive Technology -- A Highly Automated Method for Facial Expression Synthesis -- Sketch Based 3D Character Deformation -- Mean Laplace Beltrami Operator for Quadrilateral Meshes -- Multi-user 3D Based Framework for E-Commerce -- Coordinate Model for Text Categorization -- An Interface to Retrieve Personal Memories Using an Iconic Visual Language -- VR-Based Basketball Movement Simulation -- Mixed 2D-3D Information for Face Recognition -- Research on Augmented Reality Display Method of Scientific Exhibits
Electronic reproduction.
Keywords: Electronic books; Computer science; Information systems; Multimedia systems; Artificial intelligence; Computer graphics; Education